The effect of antioxidants on the course and prevention of Alzheimer’s disease on the example of vitamin E - Gawryś, Agnieszka; Cholewa, Małgorzata Maria; Kromer, Agata; Wilk, Joanna; Cichoń, Katarzyna; Zapała, Magdalena Alicja; Łapaj, Monika; Chyćko, Małgorzata; Środoń, Agnieszka; Czarnota, Julia (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the work Alzheimer’s disease is the most common cause of dementia. A small proportion of cases have a genetic etiology. Other factors that influence the development of Alzheimer’s disease include old age, family history of the disease, head trauma, hypertension in middle age, excessive body weight, diabetes, as well as elevated plasma cholesterol levels. In the course of this disease, there is accumulation of β-amyloid and intracellular neurofibrillary tangles (NETs) phosphorylated tau. Oxidative stress is a significant factor influencing induction in the course of Alzheimer’s disease. The aim of this study is to investigate the role of vitamin E on the course and prevention of Alzheimer’s disease. State of the knowledge Currently, there is no known effective treatment or prevention of Alzheimer’s disease. Given the properties of vitamin E, it seems reasonable to conduct research on its possible positive effects in the prevention and treatment of Alzheimer’s disease. Numerous studies have been conducted to determine the role of vitamin E supplementation in the course of this disease. Many of them have shown a positive effect of eating a diet rich in vitamin E or taking this vitamin in the form of supplements on slowing the rate of progression of the disease and reducing the risk of its onset. However, there are also studies in which the role of vitamin E has not been confirmed. Summary Due to its properties, vitamin E can be considered as a means to reduce the risk of developing and progressing Alzheimer’s disease, but studies conducted so far are ambiguous on this issue. Further analysis should be carried out to confirm the efficacy of vitamin E in Alzheimer’s disease.